2017
DOI: 10.1002/marc.201700307
|View full text |Cite
|
Sign up to set email alerts
|

Online Detection of Functional Groups in SEC via Quantum Cascade Laser IR Spectroscopy

Abstract: The development of coupled techniques based on chemically sensitive detectors, such as FTIR or NMR spectrometers, for size exclusion chromatography (SEC) provides sophisticated methods for determining the molecular‐weight‐dependent chemical composition in polymers. However, the detection of rare functionalities such as end groups or branching points presents a challenge, especially for online coupled SEC detection, which is based on low‐concentration chromatography. To address this issue, for the first time, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Among these hyphenated techniques, liquid chromatography coupled to Fourier transform infrared-(FT-IR), quantum cascade laser-(QCL) and NMR-spectroscopy (LC-IR/ QCL/NMR), are versatile and powerful combinations. 1,3,4 High performance liquid chromatography (HPLC) has become a powerful analytical tool for the separation of compounds since its introduction in the 1960s. 5 HPLC consists of three main modes of separation, namely (1) liquid adsorption chromatography (LAC), (2) liquid chromatography at critical conditions (LC-CC) and (3) size exclusion chromatography (SEC).…”
Section: Introductionmentioning
confidence: 99%
“…Among these hyphenated techniques, liquid chromatography coupled to Fourier transform infrared-(FT-IR), quantum cascade laser-(QCL) and NMR-spectroscopy (LC-IR/ QCL/NMR), are versatile and powerful combinations. 1,3,4 High performance liquid chromatography (HPLC) has become a powerful analytical tool for the separation of compounds since its introduction in the 1960s. 5 HPLC consists of three main modes of separation, namely (1) liquid adsorption chromatography (LAC), (2) liquid chromatography at critical conditions (LC-CC) and (3) size exclusion chromatography (SEC).…”
Section: Introductionmentioning
confidence: 99%
“…This allows the measurement of thicker samples. Thereby, the limit of detection (LOD) was reduced significantly for the SEC–QCL–IR coupling . However, such sources operate at a narrow band or can be tuned over a small range of wave numbers, typically 100–200 cm −1 .…”
Section: Introductionmentioning
confidence: 99%
“…We previously published work on an online setup combining size exclusion chromatography (SEC) and FTIR (SEC‐FTIR) and with a first prototype QCL spectrometer from Bruker Optik GmbH (Ettlingen, Germany, abbreviated as QCLS‐B) used as an online chemically sensitive detector for SEC. The measured limit of detection (LOD) was compared with results from a high‐end research IR spectrometer (Vertex 70 FTIR spectrometer from Bruker Optik GmbH) . These measurements were performed in series and allowed for a direct comparison between the two instruments.…”
mentioning
confidence: 99%
“…Analog correlation between chemical composition and molecular weight are currently conducted via SEC‐NMR indicating the needs for the acquisition of correlated information . Previous results showed that the LOD measured for the QCLS‐B was about a factor of four better than the Bruker Vertex 70 FTIR, even though a liquid nitrogen cooled MCT detector is installed on the FTIR Vertex spectrometer and a far less sensitive (balanced) LiTaO 3 detectors was used in the first prototype QCLS‐B. The QCLS‐B was based on a single external cavity QCL (EC‐QCL), which has the lowest system noise when operated in single wavelength mode .…”
mentioning
confidence: 99%
See 1 more Smart Citation